Mesianik Markus: Analisis Naratif terhadap Pelayanan dan Kesengsaraan Yesus - Lumban Raja, Bonar; Br Sinaga, Daniela Anggina (STT Injili Indonesia Medan, 2024)
Abstract: The Messianic concept of Jesus is a debatable issue. Some New Testament scholars have discussed on Messianic Mark in different perspectives. One of the classic thoughts was the Messianic secrect by Wrede. This article proposes a natrative approach on Jesus’s ministry and His death to view the Mesianic Mark. By using the narrative genre approach this article focuses on analising the teaching of Jesus, His miracle ministry and His suffering-death. Key words: Messianic, Ministry, Teaching, Miracle, Suffering, Death Abstrak: Konsep Mesianik Yesus adalah isu yang terus diperdebatkan. Beberapa sarjana Perjanjian Baru telah mendiskusikan Mesianik dalam Injil Markus dengan beragam perspektif. Salah satu pemikiran yang klasik yaitu mengenai Messianic secrect oleh Wrede. Artikel ini mengusulkan pendekatan naratif terhadap pelayanan dan kesengsaraan-kematian Yesus untuk melihat isu Mesias dalam Markus. Dengan menerapkan genre narasi, artikel ini fokus menganalisis pengajaran, mujizat dan kesengsaraan-kematian Yesus. Kata kunci: Mesianik, Pelayanan, Pengajaran, Mujizat, Kesengsaraan, Kematian